Transformational leadership model for university leaders of the Lambayeque Region - Gallo Gallo, Bertha Magdalena (2018)
Transformational leadership is effectively coupled with the development of university academic functions. The objective of the research was to build a Leadership model for university teachers in the Lambayeque region based on the Transformational Leadership approach. The specific objectives were to elaborate the theoretical framework and Historical antecedents of the leadership of the teachers in the universities through primary, secondary and tertiary sources, to identify the characteristics of the leadership of the university professor developed in their work performance, in the universities of the region, to analyze the problems of the work performance that must give Answer the university teacher, build the theoretical model based on the results obtained. The type descriptive and ethnographic study with the methods systemic, structural - functional and modeling. The results obtained gave an overview of the leadership, which has a medium - low tendency. Which indicates that the influence of the leadership in the performance of the university professor is necessary. And for which we propose a model to solve the educational problem and improve the quality of it.  Key words: Intellectual stimulation, capacity for change, research, didactics, university extension.